Advanced modeling for transit operations and service planning - Lam, William H. K.; Bell, Michael G. H. (Emerald, 2002)
In this title, experts in public transport address the current problem of improving public transit systems by taking advantage of new technologies and advanced modelling techniques. The key areas open to improvement are service planning and operations management.